Dnmt2-dependent methylomes lack defined DNA methylation patterns - Raddatz, Günter; Guzzardo, Paloma M.; Olova, Nelly; Fantappié, Marcelo Rosado; Rampp, Markus; Schaefer, Matthias R.; Reik, Wolf; Hannon, Gregory J.; Lyko, Frank (Proceedings of the National Academy of Sciences of the United States of America, 2013)
Several organisms have retained methyltransferase 2 (Dnmt2) as their only candidate DNA methyltransferase gene. However, information about Dnmt2-dependent methylation patterns has been limited to a few isolated loci and the results have been discussed controversially. In addition, recent studies have shown that Dnmt2 functions as a tRNA methyltransferase, which raised the possibility that Dnmt2-only genomes might be unmethylated. We have now used whole-genome bisulfite sequencing to analyze the methylomes of Dnmt2-only organisms at single-base resolution. Our results show that the genomes of Schistosoma mansoni and Drosophila melanogaster lack detectable DNA methylation patterns. Residual unconverted cytosine residues shared many attributes with bisulfite deamination artifacts and were observed at comparable levels in Dnmt2-deficient flies. Furthermore, genetically modified Dnmt2-only mouse embryonic stem cells lost the DNA methylation patterns found in wild-type cells. Our results thus uncover fundamental differences among animal methylomes and suggest that DNA methylation is dispensable for a considerable number of eukaryotic organisms.
Gesehen am 11.01.2022